2013
DOI: 10.1177/1938640013477452
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematics of the Talocrural and Subtalar Joints With Functional Ankle Instability During Weight-Bearing Ankle Internal Rotation

Abstract: Functional ankle instability (FAI) may involve abnormal kinematics. However, reliable quantitative data for kinematics of FAI have not been reported. The objective of this study was to determine if the abnormal kinematics exist in the talocrural and subtalar joints in patients with FAI. Five male subjects with unilateral FAI (a mean age of 33.4 ± 13.2 years) were enrolled. All subjects were examined with stress radiography and found to have no mechanical ankle instability (MAI). Lateral radiography at weight-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…53,55 Lateral displacement of the fibula widens the distal tibiofibular joint, affecting the mortise structure, and is associated with excessive talar rotation. Previous in vivo studies have shown an increase in talar anterior translation, 6,32 inversion, 6 and internal rotation 6,31 in the ankles with CAI. Thus, complex analyses that include examination of talocrural joint alignment or kinematics, as well as investigation of the distal tibiofibular joint, will be required in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…53,55 Lateral displacement of the fibula widens the distal tibiofibular joint, affecting the mortise structure, and is associated with excessive talar rotation. Previous in vivo studies have shown an increase in talar anterior translation, 6,32 inversion, 6 and internal rotation 6,31 in the ankles with CAI. Thus, complex analyses that include examination of talocrural joint alignment or kinematics, as well as investigation of the distal tibiofibular joint, will be required in the future.…”
Section: Discussionmentioning
confidence: 98%
“…31,32,56 Average interobserver difference of the anatomical coordinate systems was 0.35 mm in translation and 0.76° in rotation, and average intraobserver difference was 0.35 mm in translation and 0.85° in rotation (FIGURE 1). 56…”
Section: Anatomical Coordinate Systemsmentioning
confidence: 98%
“…Ankle range of motion (ROM) was simulated about three axes of rotation: dorsi-plantar flexion, inversion-eversion and internal-external rotation by manipulating the implanted tibia rod M a n u s c r i p t 6 with the toes taped to the stationary treadmill. DF images were acquired at 100 Hz.…”
Section: Simulation Of Rotational Profiles and Gaitmentioning
confidence: 99%
“…Intra-cortical pins with reflective markers have independently tracked the tibia, talus, and calcaneus [4,5], but this approach is highly invasive. Other studies have used single plane fluoroscopy to study invivo motions of the ankle [6][7][8]. However, out-of-plane motions, such as axial rotation of the subtalar joint, cannot be accurately measured with single plane fluoroscopy [9].…”
Section: Introductionmentioning
confidence: 99%
“…The radiographic nature of fluoroscopy also allows for gait analysis during shoe wear, brace wear, and orthotic usage that is not achievable using optical motion analysis with external markers. Two-dimensional (2D) in vivo fluoroscopic analysis of the hindfoot has been reported by both our group and other authors [14][15][16][17][18][19][20][21][22]. While these 2D analyses are valuable for quantifying single plane dynamics, they lack the ability to determine out of plane motions, such as axial rotation of the subtalar joint [23,24].…”
Section: Introductionmentioning
confidence: 99%